Fixed vs. Free-text Documentation of Indication for Antibiotic Orders - Javaid, Waleed (Open Forum Infect Dis, 2017)
BACKGROUND: Requiring indications for antimicrobial orders can allow stewardship programs to evaluate adherence to guidelines and assess outcomes. We extracted indication data from our institution’s EPIC system and found that in a 29-month time frame there were 12,218 uniquely entered indications. Only 136 of these were standardized drop-down (fixed) menu options; the rest were entered manually (free-text). Enormous variation in these uniquely typed entries emphasizes the value and necessity of fixed indication options to allow for better evaluation of stewardship program outcomes. METHODS: We evaluated the 718 most commonly used indications accounting for a total of 113,741 unique antibiotic orders for 42,665 patients. We excluded indications used for less than 36 orders during the study period. We analyzed the characteristics of these orders to identify opportunities for improvement in indication documentation and developed a new list of less than 200 indications that could account for nearly all of the various indications entered. RESULTS: 66,404 (58%) orders were placed using fixed options available in the menu (Figure 1). 32,427 (29%) orders were placed with no indication listed. The remaining 14,910 (13%) orders were documented with free-text indications. Within these manual entries, 59% were identical or nearly identical to an option that was available in the drop down menu. 37% of free-text indications could not be appropriately placed with an option available in the menu. For example, the menu contained a fixed option for “Severe C. difficile infection” forcing all non-severe cases to be entered as varied free-text alternatives (Figures 2 and 3). CONCLUSION: In our sample, use of fixed menu options was high but robust evaluation of proper antimicrobial use was substantially limited by failure to document indication and free-text entry by providers. Free-text entry and blank fields can be used as quality metrics, with high use indicating poor quality. We recommend that standard comprehensive indication lists are developed, providers are encouraged and empowered to utilize menu options consistently, and computerized order systems are programmed to prevent orders from being placed without an indication listed. DISCLOSURES: All authors: No reported disclosures.